Religion and social transformations - Herbert, David (Religion today : tradition, modernity and change, 2001)
Like the other volumes in this series, this book has been compiled primarily with the needs of Open University undergraduates in mind. However it should also be of use to other readers who would like to know more about the place of religion in the world today.